CircRNA_ACAP2 Suppresses EMT in Head and Neck Squamous Cell Carcinoma by Targeting the miR-21-5p/STAT3 Signaling Axis - Ma, Chuan; Shi, Tingting; Qu, Zhuli; Zhang, Aobo; Wu, Zuping; Zhao, Huaqiang; Zhao, Haoming; Chen, Hongyu (Frontiers in Oncology, 2020)
CircRNAs contain microRNA (miRNA) specific binding sites and can function as miRNA sponges to regulate gene expression by removing the inhibitory effect of an miRNA on its target gene. MiR-21-5p has been reported to be involved in the development of Head and Neck Squamous Cell Carcinoma (HNSCC) and plays an active role in the activation of epithelial-mesenchymal transition (EMT). However, the upstream regulatory mechanism and downstream targets of miR-21-5p in tumor cells remains unknown. CircRNA_ACAP2 inhibits the function of miR-21-5p through binding to its specific binding sites in HNSCC cells. Overexpression of CircRNA_ACAP2 inhibits the proliferation and migration of HNSCC cells, while downregulation of CircRNA_ACAP2 does the opposite. STAT3 is a direct target gene of miR-21-5p and a transcription factor of ZEB1. We improve that CircRNA_ACAP2 functions as a tumor suppressor gene in HNSCC, and its function is regulated via miR-21-5p/STAT3 signal axis.